(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This paper examines the concept of remission in oncological diseases as an important stage following the completion of anticancer therapy. The main forms of remission—partial and complete—are described, along with their clinical features and diagnostic criteria. Special attention is paid to issues of body recovery after therapy, including recommendations on nutrition, physical activity, and lifestyle. The necessity of regular medical follow-up during remission and factors influencing the risk of disease recurrence are also discussed. The role of the patient in maintaining a stable state of health and reducing the risk of cancer relapse is emphasized.